Experimental hermodynamic arteriosclerosis of the coronary artery - Palma, E C; Passano de Moizo, M; Guevara, A.; Perillo, W; Fernández, E; González Viera, P; González Viera, P (Cirugía del Uruguay, 2020)
Work of the Prof E Palma Surgical Clinic and the Institute of Pathology of the Prof J J Stable School of Medicine